The attempted formation of quaternary centers via a novel intramolecular para-C-alkylation and the use of the aza-Ireland-Claisen rearrangement in the attempted formation of adjacent stereocenters - Jebreen, Joseph Shiban (University of Ottawa (Canada), 2004)
The formation of quaternary centers is a formidable challenge. Once these quaternary centers become part of a spirocyclic system, the project becomes even more challenging. The intramolecular para-C-alkylation has been previously used with success. However, no literature precedence is available for an asymmetric version of this reaction. The attempts in synthesizing molecules similar to 123 by using such methodologies are described herein.* Also described is a second project which involved the effective use of the aza-Ireland-Claisen rearrangement in constructing medium-sized rings. These rings can be easily hydrolyzed to produce useful, functionalized synthetic fragments 157 containing two adjacent stereocenters as shown below.* *Please refer to dissertation for diagrams.
Keywords: Chemistry, Organic.